Origin of Gravity Lows South of the 85∘E Ridge (Central Basin of the Indian Ocean) - Bulychev Andrei; Dubinin Evgenii; Ivanenko Aleksandr; Levchenko Oleg; Veklich Ilya; Kosnyreva Mariya; Shaikhullina Anzhela (Russian Journal of Earth Sciences)
The 85∘E Ridge associated by the free-air gravity low into a meridional orientation. However, there are two gravity lows south between of 4∘N and 3∘S the nature of which remains a subject of discussion. This article presents the results of density and magnetic modeling based on the data of the expedition SO258/2 with RV Sonne. An analysis of the modeling results with seismic data showed that the nature of gravity lows is associated with the process of serpentinization, and these lows are not a continuation of the 85∘E Ridge.